PRICE LEVEL ACCOUNTING. - Weber, G. Fred (The Accounting Review, 1960)
As the economy changes there must be changes in accounting practices. Accounting cannot serve a useful function by remaining static in a dynamic economy. New rules and methods must be devised better to account for assets, liabilities, and net worth and to report on financial status, earnings, and the utilization of resources. These are desirable goals even in a static economy, they become imperative in one that is shifting and changing. Accounting principles are defined as fundamental truths, concepts, or basic assumptions such as the cost principle and principles of objectivity, conservatism, consistency, disclosure, the stable dollar. The problem of price level changes concerns owner equity, not assets, and certainly not fixed assets in particular. This can be demonstrated by a simple example. On January 1st of a given year an enterprise borrows $50,000. It invests the proceeds of the loan in merchandise, sells all the merchandise for $60,000 net of selling cost during the year, and repays the loan at December 31st. This enterprise would have increased its purchasing power or productive capacity by $10,000, less any interest paid on the loan. If the enterprise had operated solely on this loan and if there were no other transactions, it would have no justification in taking any kind of inflation loss against this income regardless of how great the price level rise may have been.